A Strategi Rekruitmen Crew Kapal di PT. Lotus Prakasa Lines Surabaya - Moh Ilham Isyraqi; Sudirman Sudirman; Carlos Lazaro Prawirosastro (Universitas Maritim AMNI Semarang, 2024)
The aim of this research is to find out what obstacles are faced by PT. Lotus Prakasa Lines Surabaya in implementing ship crew recruitment strategies. This implementation was carried out at the PT. Lotus Prakasa Lines Surabaya office, during which the author carried out ground practice (PRADA) from August 2023 to February 2024. The source of data obtained was primary data which was directly obtained from the research site by means of observation, direct interviews with company employees as well as secondary data sources, namely literature related to the title of the thesis. The results of this research indicate that the implementation of ship crew recruitment at PT Lotus Prakasa Lines Surabaya contained several obstacles which resulted in the ship crew recruitment process being slow. At PT Lotus Prakasa Lines Surabaya, among other things, crew selection that is in accordance with the owner's request is not yet timely, certificates and crew documents that have expired or are close to expiring before the contract expires, and communication between Lotus and the owner is slow due to the time difference between Indonesia and overseas.